Pengaruh Self efficacy Terhadap Kemampuan Problem Solving Mahasiswa Akhir Fakultas Psikologi di Universitas Muhammadiyah Jember dalam Mengerjakan Tugas Akhir - Wardanis, Ina; Ervina, Iin; Linsiya, Ria Wiyatfi (Jurnal Psikologi, 2024)
Problem solving is a search for a solution carried out by individuals using various methods to solve the problems being faced. Meanwhile, self-efficacy is an individual's self-confidence related to one's ability to complete the tasks or problems being faced by the individual. This type of research is quantitative. The respondents in this research were final students who were working on their thesis at the Faculty of Psychology, UM Jember. The results of this research show that there is a significant influence between the self-efficacy variables and problemsolving abilities where the sig. 2-tailed 0.000 < 0.05 means H0 is rejected and H1 is accepted, which means there is a significant influence between self-efficacy and problemsolving abilities. The variable contribution of 0.935 as seen from R square can be interpreted to mean that self efficacy has a contribution effect of 93.5% on variable Y and the other 6.5% can be influenced by other factors outside of variable habits, sense of security, economy, uncertainty, and perception (Rinawati, 2011).